Front Cover: Reactivity of CO and C2H4 on Bimetallic PtxAg1‐x/Pt(111) Surface Alloys Investigated by High‐Resolution X‐ray Photoelectron Spectroscopy (ChemPhysChem 12/2018). Issue 12 (7th June 2018) - Bauer, Udo; Späth, Florian; Düll, Fabian; Bachmann, Phillip; Steinhauer, Johann; Steinrück, Hans‐Peter; Papp, Christian
Abstract : The Front Cover shows the two metals platinum and silver that form a bimetallic surface alloy in the first layer. On this model catalyst, depending on the relative Ag content, the adsorption strength of CO can be enhanced and C−H bond activation is achieved much easier. More information can be found in the Article by U. Bauer et al. onpage 1432 in Issue 12, 2018 (DOI:10.1002/cphc.201800044 ).